Features of Roasted Green Coffee Beans: A Review - Das, Monalisa; Mohanty, S N (International Journal of Psychosocial Rehabilitation, 2025)
The advancement of food preparation component installations involves the assessment of the mechanical features of food components. The understanding of customers as well as the layout specifications of manufacturing equipment is influenced by features such as the length, structure and color. Liquid movement, humidity, density and resting angle. During this study, improvements in microwave defrosting variables analyzed the technology characteristics of green/unroasted coffee beans. The system variables were roasted energy (300, 450, 600 W) including time (5.0, 10.0, 15.0, &20.0 min) and the coffee beans were evenly spread with such a sequence of cooking. Satisfactory roasting with a signature coffee pink color, was deemed achieved. Water behavior of the potatoes has been identified under safe, laboratory limits (aw<0.6), and its higher water content can also be verified (0.14±0.06 to 0.96±0.12% db.). True and large volume density decreased considerably with the microwave power increase. Nevertheless, the results, including reposition angle, have improved from 300 to 600 W (17.84 to 25.50 °) and porosity (0.454-0.559). The globular variety of roasted coffee with no specified pattern varied from 0.659-0.707. The browning index (BI) of the specimens showed a certain increase in microwave energy, which was probably caused by the discoloration of the beans. The same pattern with a rise in roasting time has been identified. The BI was collected in the range of 67-72 for the most desired specimens. According to observations, the most desirable aspect and low processing time were baked coffee beans at 450 W for 5 min.